2016
DOI: 10.1371/journal.pgen.1005856
|View full text |Cite
|
Sign up to set email alerts
|

TDM1 Regulation Determines the Number of Meiotic Divisions

Abstract: Cell cycle control must be modified at meiosis to allow two divisions to follow a single round of DNA replication, resulting in ploidy reduction. The mechanisms that ensure meiosis termination at the end of the second and not at the end of first division are poorly understood. We show here that Arabidopsis thaliana TDM1, which has been previously shown to be essential for meiotic termination, interacts directly with the Anaphase-Promoting Complex. Further, mutations in TDM1 in a conserved putative Cyclin-Depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(77 citation statements)
references
References 45 publications
1
74
0
2
Order By: Relevance
“…). Previous studies demonstrated that OSD1 is an APC/C inhibitor, while TDM1 is present throughout meiosis and its activity must be inhibited during meiosis I (Cromer et al ., ; Cifuentes et al ., ). Our qRT‐PCR data show that the expression of both genes is elevated in apc8‐1 compared with wild‐type, indicating that there may be a feedback mechanism between APC/C and its regulators.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…). Previous studies demonstrated that OSD1 is an APC/C inhibitor, while TDM1 is present throughout meiosis and its activity must be inhibited during meiosis I (Cromer et al ., ; Cifuentes et al ., ). Our qRT‐PCR data show that the expression of both genes is elevated in apc8‐1 compared with wild‐type, indicating that there may be a feedback mechanism between APC/C and its regulators.…”
Section: Discussionmentioning
confidence: 97%
“…The essential function of APC/C subunits in plants has limited our understanding of their function during chromosome segregation. Evidence suggests that Arabidopsis TDM1 is an APC/C component and is required for the termination of meiosis II (Cromer et al, 2012;Cifuentes et al, 2016). OSD1 promotes entry into the second meiotic division, likely to be through inhibition of APC/C activity (Cromer et al, 2012).…”
Section: Conservation and Divergence Of Apc/c Activity In Meiosis Amomentioning
confidence: 99%
See 1 more Smart Citation
“…SDS and TAM build active kinase complexes with CDKA;1, the Arabidopsis Cdk1/Cdk2 homolog, that is the main cell cycle regulator in Arabidopsis (Cromer et al, 2012;Nowack et al, 2012;Cifuentes et al, 2016). A function of CDKA;1 in meiosis is supported by the analysis of weak loss-of-function mutants, which are completely sterile (Dissmeyer et al, , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For AtREC8, there is currently no alternative as the single other gene known to be required for monopolar orientation of kinetochores is SCC3, which is also expressed mitotically and thus the corresponding mutation would affect regular development [19]. Two alternatives to osd1 can be used to create MiMe, tam and TDMΔD [17,21]. Finally, besides AtSPO11-1, several genes have been shown to be essential for initiation of meiotic recombination through DNA double-strand break formation (AtSPO11-2, PRD1, PRD2, PRD3/PAIR1, DFO and MTOPVIB) [22][23][24][25][26], but are not yet tested to create the MiMe phenotype.…”
Section: Introductionmentioning
confidence: 99%